Clinical outcomes of fractionated stereotactic radiotherapy for uveal melanoma – a Polish single-centre experience - Deja, Adam; Baluch, Paulina; Wróblewska-Zierhoffer, Marta; Zwolińska, Emilia; Radomiak, Maria; Milecki, Piotr; Rospond-Kubiak, Iwona (Contemporary Oncology/Współczesna Onkologia, 2025)
The aim of the study is to present the results of the first Polish cohort of patients treated with fractionated stereotactic radiotherapy (fSRT) for large and/or juxtapapillary uveal melanoma (UM). Material and methods: The medical records of the patients who underwent the fSRT for UM in Poznań (cooperation between the Department of Ophthalmology, Poznań University of Medical Sciences and Greater Poland Cancer Centre) in 2014–2020 were retrospectively reviewed. The diagnosis was made in each case after detailed clinical examination, ultrasound and/or choroidal biopsy in selected patients. The irradiation protocol was to deliver 50 Gy in 5 fractions. Results: We identified 27 patients, 12 men, 15 women, with a median age of 61.5 years. The median longitudinal basal diameter of treated tumours was 11.7 mm (range 5.2–17.8 mm), median thickness – 7.5 mm (range 1.7–9.7 mm). The median follow-up was 38 months (range 5–101 months). We observed neovascular glaucoma in 9 (34%) patients, which was the reason for globe removal in 3 (11%) of them. There was one local tumour recurrence (3.8%) with extraorbital extension 6 years post-treatment. Local tumour control in our cohort was 96.2%. By the study end, 5 (18.5%) patients died, including 3 (11%) of metastatic disease. The final visual acuity was logMAR 0.3 or better for 3 patients (11%). Conclusions: As reported also by other authors, fSRT could be a useful treatment modality for selected large and/or juxtapapillary melanomas.